Alternative Approaches for Providing Financial Provision for Mine Rehabilitation and Closure - Grant-Stuart, DJ (Mine Closure 2008: Third International Seminar on Mine Closure, 2008)
The requirement for financial provision for mine closure is intended to manage or limit the risk of the Government (i.e. the taxpayer) inheriting the environmental liability for decommissioned mines that have not been correctly closed or rehabilitated. While many countries still do not have comprehensive or formal mine closure legislation, the requirements for financial closure provision in those countries or states that do have such legislation vary considerably. Depending on the country or state in which a particular mine may be located, financial provision may take the form of a trust fund; cash deposit; letter of credit; surety bond; or any other guarantee. Furthermore, the methods used for determining the quantum of the required financial provision vary significantly across the globe. For example, the amount of financial provision can be calculated from a simple rate per unit area in some cases, or it could be estimated from a schedule of quantities with specific rates for measured items of work. The South African Minerals and Petroleum Resources Development Act (Act 28 of 2002) requires that a risk- based approach to determining the financial provision be adopted by the mining company. A guideline document was developed by the Department of Minerals and Energy (DME) to assist the regulator in assessing adequacy of financial provision, and recommends that the risk class of a particular mine is determined from the throughput and type of mineral mined. Then, depending on the class of mine and level of information available, the method of determining the amount of financial provision may be based either on a master rate per unit area, or it may be calculated from a more rigorous analysis using a measured schedule of quantities priced at current commercial rates. Either way, the object is to ensure that there are sufficient funds available at any stage in the life of a mine to cover the cost of rehabilitation and closure. Needless to say, there is an understandable reluctance on the part of many mines to set aside large sums of capital in an inaccessible trust fund established for this purpose. The purpose of this paper is to explore means to ensure that the regulatory requirement for financial provision is met, while at the same time avoiding the need to “lock up” funds that could otherwise be put to productive use. The question is raised whether it is appropriate to apply the same methods of determining the financial obligation across the board to different types of mine infrastructure. Legislative requirements, the means of providing financial guarantees and the methods of calculating the quantum of financial provision used in various countries are examined with a view to applying the most advantageous practice to all parties, while still complying with South African legal requirements.